Reviving the kapis industry in Oton, Iloilo an evaluation of the stock enhancement project - Guevara, Pablo S., Jr. (Miagao, Iloilo University of the Philippines in the Visayas, 2001)
A study was made to determine the changes in the Kapis industry of Oton, Iloilo for the past decades and to evaluate the kapis stock enhancement in Oton. The municipality of Oton has been traditionally a source of kapis for shellcraft manufacturers. However, in the late 1980's, there was a marked decline in its kapis harvest. This has been attributed to excessive gathering of kapis by divers using compressors and trawl fishing, which destroyed that habitats of kapis. The municipal government of Oton and SEAFDEC started a stock enchancement project to revive the kapis industry by transplanting 800 pieces of broodstock in Brgy Tarpiche, Oton. Monitoring showed lval and juvenile abundance after several months from the release of stock. The final stock assessment, however, showed very few live shells in the stocking area. There was little support from the community because of the minimal participation of the stakeholders in the panning and implementation of the project. An important component of a program to revive the kpis industry in Oton is effective law enforcement in order to eliminate illegal fishing practices that are causing damage to the kapis stock and its habitat.
Special Problem (MMA) -- Miagao, Iloilo : University of the Philippines in the Visayas, 2001.